1994
DOI: 10.1002/polb.1994.090321407
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and transport of water in nylon‐6 films

Abstract: Sorption and transport properties of water through films of Nylon‐6 were obtained at 5, 23, and 40°C. Commercially available films were used and a Cahn electrobalance was employed for measuring the water uptake by the polymer samples. Values of the water sorption isotherms are accurately described by the Langmuir/Flory‐Huggins dual‐mode sorption model. At water activity values below 0.15, the volume fraction of water described by the Langmuir portion of the model was greater than the Flory‐Huggins population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 25 publications
7
53
0
1
Order By: Relevance
“…7,16,19,24 Only one particular study reported a maximum for the diffusion coefficient at an RH of 50% at 23°C. 3 Moreover, the magnitude of the obtained diffusion coefficient is in agreement with values reported in the literature (1 × 10 −14 to 1 × 10 −13 m 2 s −1 at 25°C 8 ). In contrast with previous studies on nylon-6.6, a highly nonlinear relation between the moisture content and the diffusion coefficient is observed.…”
Section: ■ Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…7,16,19,24 Only one particular study reported a maximum for the diffusion coefficient at an RH of 50% at 23°C. 3 Moreover, the magnitude of the obtained diffusion coefficient is in agreement with values reported in the literature (1 × 10 −14 to 1 × 10 −13 m 2 s −1 at 25°C 8 ). In contrast with previous studies on nylon-6.6, a highly nonlinear relation between the moisture content and the diffusion coefficient is observed.…”
Section: ■ Resultssupporting
confidence: 81%
“…In the literature moisture content values are reported in the range from 4% 17 up to 10%. 3,7,16 The moisture content increases disproportional above relative humidities of 65% with respect to the lower humidities. Despite the differences in raw material (e.g., molecular weight) and processing conditions (influences of crystallinity 30 ), the shape of the obtained sorption isotherm is similar to the ones in literature.…”
Section: ■ Materialsmentioning
confidence: 99%
“…137 These results are in agreement with two modes of sorption identified in water uptake measurements with a Cahns electrobalance. 138 However, NMR T 1q measurements reveal three types of water (Fig. 13).…”
Section: State Of Watermentioning
confidence: 99%
“…In practice, it can be representative of the sorption of water in highly hydrophilic polymers (Hernandez and Gavara, 1994;Hernandez et al, 1992): initially, the water molecules are strongly sorbed in specific sites corresponding to polar groups, then at higher pressures, the clustering process may occur.…”
Section: Bet Modementioning
confidence: 99%